Corporate mergers and security returns - Dennis, Debra K.; McConnell, John J. (Journal of Financial Economics, 1986)
An examination of rates of return and dollar value returns for various classes of merging firms' securities indicates that acquired companies' common stockholders, convertible and non-convertible preferred stockholders, and convertible bondholders gain in merger, as do acquiring companies' convertible preferred stockholders. Acquired companies' non-convertible bondholders and acquiring companies' convertible and non-convertible bondholders and non-convertible preferred stockholders neither gain nor lose. There is no evidence that acquiring companies' common stockholders lose and there is statistically reliable evidence that they gain. Additionally, the dollar value of both acquired and acquiring firms increase, as does the dollar value of the combined acquired and acquiring companies.